Além dos limites da justiça : a crítica de Sandel a Rawls - Lessa, Jaderson Borges (2018)
The aims of this research on the criticism of Michael Sandel to John Rawls it is to investigate the possibility to carry out another solution the problem of the priority of the right over the good, about the limits of the theory of justice and of political liberalism. This aims signals an attempt to solve a problem internal justice as fairness but became the target of external critics, who saw in this situation their practical and conceptual limits. Even acknowledging external criticism, the proposed solution to the limits presented involves an internal response. The proposal includes: α) the displacement of the problem of priority to the problem of congruence; β) the affirmation of the relevance of conceptions of good, both from the moral and political point of view, of a conception of justice; γ) the recognition that a rejection of a vision of good could weaken political institutions. The implication of this perspective is that any absolute understanding of these perspectives is undone if emphasized the elements of justice and good in the perspective of congruence. Given these objectives and proposals, the research plan is based on the state of how this question is found in the work of Rawls, either in terms of priority or of congruence. Then are the critical considerations that Sandel presents as limits to the realization of that theory of justice and that form of political liberalism. Namely, that justice cannot be primary and that political liberalism leads to a loss of the politics of good (common, public). The result is a "procedural republic". The last part is to demonstrate that the problem of congruence – that of showing the possibility of a theory of justice finding a place within the conceptions of good – it is not rejected by liberalism. This idea reinforces the possibility of Rawls's theory goes beyond the limits indicated by Sandel.